2019
DOI: 10.2463/mrms.mp.2017-0135
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating between Glioblastoma and Primary CNS Lymphoma Using Combined Whole-tumor Histogram Analysis of the Normalized Cerebral Blood Volume and the Apparent Diffusion Coefficient

Abstract: Our results suggest that whole-tumor histogram analysis of nCBV and ADC combined can be a valuable objective diagnostic method for differentiating between GBM and PCNSL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 49 publications
(68 reference statements)
0
26
1
Order By: Relevance
“…Detailed information of excluded studies is described in the Supplementary Materials. One further relevant study was also identified, resulting in a final total of 22 studies investigating the diagnostic performance of MRI for differentiating PCNSL from glioblastoma, with these studies covering 1182 patients.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Detailed information of excluded studies is described in the Supplementary Materials. One further relevant study was also identified, resulting in a final total of 22 studies investigating the diagnostic performance of MRI for differentiating PCNSL from glioblastoma, with these studies covering 1182 patients.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of MRI sequences were used in various combinations (Table ), with the most commonly used sequences being DWI in 14 studies, DSC in nine studies, and DCE in four studies . The other less‐commonly used sequences were ASL in four studies, SWI in four studies, MRS in three studies, and IVIM in two studies .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations